Metabolism: A Novel Shared Link between Diabetes Mellitus and Alzheimer’s Disease - Yanan Sun; Cao Ma; Hui Sun; Huan Wang; Wei Peng; Zibo Zhou; Hongwei Wang; Chenchen Pi; Yingai Shi; Xu He (Journal of Diabetes Research)
As a chronic metabolic disease, diabetes mellitus (DM) is broadly characterized by elevated levels of blood glucose. Novel epidemiological studies demonstrate that some diabetic patients have an increased risk of developing dementia compared with healthy individuals. Alzheimer’s disease (AD) is the most frequent cause of dementia and leads to major progressive deficits in memory and cognitive function. Multiple studies have identified an increased risk for AD in some diabetic populations, but it is still unclear which diabetic patients will develop dementia and which biological characteristics can predict cognitive decline. Although few mechanistic metabolic studies have shown clear pathophysiological links between DM and AD, there are several plausible ways this may occur. Since AD has many characteristics in common with impaired insulin signaling pathways, AD can be regarded as a metabolic disease. We conclude from the published literature that the body’s diabetic status under certain circumstances such as metabolic abnormalities can increase the incidence of AD by affecting glucose transport to the brain and reducing glucose metabolism. Furthermore, due to its plentiful lipid content and high energy requirement, the brain’s metabolism places great demands on mitochondria. Thus, the brain may be more susceptible to oxidative damage than the rest of the body. Emerging evidence suggests that both oxidative stress and mitochondrial dysfunction are related to amyloid-β (Aβ) pathology. Protein changes in the unfolded protein response or endoplasmic reticulum stress can regulate Aβ production and are closely associated with tau protein pathology. Altogether, metabolic disorders including glucose/lipid metabolism, oxidative stress, mitochondrial dysfunction, and protein changes caused by DM are associated with an impaired insulin signal pathway. These metabolic factors could increase the prevalence of AD in diabetic patients via the promotion of Aβ pathology.